2018
DOI: 10.31584/jhsmr.2018.36.4.22
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Under-Prescription in Elderly Type 2 Diabetic Patients in the Primary Care Unit of a University Hospital

Abstract: Objectives: This study aimed to assess the prevalence of under-prescription among elderly type 2 diabetic patients in the primary care unit of a university hospital in southern Thailand and identify the associated factors.Material and Methods: A 1-year retrospective medical record review was conducted in elderly type 2 diabetic patients treated continuously in the primary care unit. Under-prescription was the primary outcome assessed from criteria developed from the START criteria (2015), Thailand’s clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Most people with DM have MM or complications that can include hypertension, dyslipidaemia, nephropathy, neuropathy, retinopathy, cardiovascular, cerebrovascular or peripheral vascular diseases and as a result receive multiple medications. Correspondingly, PIP among people with DM has been reported to be high in a range of international studies [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Most people with DM have MM or complications that can include hypertension, dyslipidaemia, nephropathy, neuropathy, retinopathy, cardiovascular, cerebrovascular or peripheral vascular diseases and as a result receive multiple medications. Correspondingly, PIP among people with DM has been reported to be high in a range of international studies [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Thailand was based at primary care unit of Songlanagarind Hospital to explore prevalence of under-prescription of diabetes medication and associated factors with it. The study showed that the prevalence of under prescription among elderly type 2 diabetes was 84.5% , however, having number of medications received increased, and a status of cardiovascular diseases are found to have lower risk of under prescription (Ananchaisarp et al, 2018).…”
Section: Factors Of Non-adherencesmentioning
confidence: 93%